Japan, the Olympics and the COVID-19 pandemic - Macnaughtan, H. (East Asia Forum, 2020)
Japan`s path to hosting the Summer Olympics has had more than its fair share of twists and turns. The Tokyo 1940 Olympics were cancelled. Since their inception in 1896 the Olympics have been cancelled only three times: 1916, 1940 and 1944, all in wartime. The Games have weathered political boycotts and acts of terrorism, but in 2020 they have been postponed for the first time because of a pandemic. The viability of 2021 depends on Japan`s ability to control COVID-19 domestically. The current number of cases and deaths in Japan is comparatively low (17,916 cases and 953 deaths), but policymakers must ensure that lingering criticism and any second wave is effectively managed. The viability of 2021 also hinges on how COVID-19 is managed globally, particularly in nations that are `big hitters` at the Olympics. The United States, Great Britain, Russia, France and Italy were in the top 10 medal-winning nations at Rio 2016. They also rank high as nations most impacted by coronavirus-related deaths, with the full impact of COVID-19 yet to be determined. A downsized Olympics without the participation of athletes from major competing countries is likely to be unpopular, but Tokyo Governor Yuriko Koike has announced that the Japanese government and Tokyo 2020 organising committee are contemplating a simplified Games. If Japan had COVID-19 under control by July 2021, with strict quarantine measures at the border, the Games could run in a viable format: for example, behind closed doors or with reduced spectators. Lessons learned from Japan`s hosting of the 2019 Rugby World Cup, including its crisis response to the typhoon that struck during the tournament, are still valuable but possibly less valid amid the new challenges of a global pandemic. If Tokyo 2020 is downsized or cancelled, the legacy will be how to manage a `new normal` world for the Olympics and other sport mega-events. Beijing 2022 is scheduled to start five months after Tokyo 2020 ends and Paris 2024 two years thereafter, so lessons from Japan will be paramount.